MIND MAPS AS A MEANS OF VISUALIZATION OF EDUCATIONAL TASKS - Blakh, Valeriia; Yurina, Yuliia; Oksana ,; Sagan, Olena; Liba, Oksana (Revista Inclusiones, 2020)
The article deals with the problem of usage of means and methods of information presentation, which give possibility to visualize it effectively for further comprehension and structuring. The methodology of creating mind maps, criteria of their effective application in educational process are proved. As a part of experiment, the impact of the mind maps method on the results in education is studies. In this respect three spheres of educational tasks (according to B. Bloom): cognitive, affective and psychomotor are taken in consideration. The results of the investigation showed positive changes in educational results and effectiveness in the application of mind maps both of a traditional type and as a digital app.